Movement behaviour patterns in adults with haemophilia. (March 2020) - Timmer, Merel A.; Veenhof, Cindy; de Kleijn, Piet; de Bie, Rob A.; Schutgens, Roger E. G.; Pisters, Martijn F.
Background: Joint bleeds are the hallmark of haemophilia, and can lead to disabling haemophilic arthropathy. Consequently, the movement behaviour of adults with haemophilia differs from that of healthy adults. It seems unlikely that a single outcome is able to reflect all relevant information regarding movement behaviour. The aim of the current study was to identify patterns of movement behaviour within persons with haemophilia (PWH) and compare clinical characteristics between patterns of movement behaviour. Methods: A total of 105 PWH [70% severe haemophilia; median age 43 years (30.0–54.0)] were included in the study. Hierarchical cluster analysis was used to identify patterns of movement behaviour. Clustering variables included seven parameters of movement behaviour: sitting, standing, walking, biking, running, frequency of active bouts and length of active bouts. Clinical characteristics included age, severity of haemophilia, joint health, physical functioning and pain. Clinical characteristics were compared between identified clusters by Kruskall–Wallis test. Movement behaviour was assessed with the Activ8 accelerometer, joint health was assessed on the Haemophilia Joint Health Score, physical functioning on the Haemophilia Activity List and the 40 m self-paced walk test and pain on the Numerical Pain Rating Score. Results: Cluster analysis identified three clusters, which were defined as: 'sedentary' (57%), 'bikers and runners' (22%) and 'walkers' (20%). The 'bikers and runners' showed better joint health and experienced fewer limitations in activities than the 'walkers' and the 'sedentary'. The 'walkers' perceived fewer limitations in activities than the 'sedentary', with comparable joint health. We did not identify differences in pain, walking speed and age between the clusters. Conclusions: We identified three patterns of movement behaviour. The majority of PWH was identified as sedentary, whereas less sitting and regular walking during the day seemed to be more beneficial.